PRODUCTION, OPTIMIZATION AND ENZYMATIC REMOVAL OF OLIGOSACCHARIDES FROM SOYMILK BY ALPHA GALACTOSIDASE ENZYME FROM ROCK SOIL PSEUDOMONAS SP. MCCMB3 - HEMA. T. A; HELEN PAPPA. T (International Journal of Pharma and Bio Sciences, 2012)
Alpha-galactosidase is a glycoside hydrolase enzyme that hydrolyses the terminal alpha-galactosyl moieties from glycolipids and glycoproteins. Pseudomonas sp. MCCMB3 an alpha galactosidase producer was isolated from the rock soil of Kulasekaram, Kanyakumari district, South India. Totally 10 strains were isolated, when compared with other strains, predominant enzyme activity has been observed in the strain of Pseudomonas sp. MCCMB3. The maximum amount of enzyme was produced using nutrient broth during optimization. Environmental and nutritional parameters were optimized for the enhanced enzyme production. The enzyme production was maximum at pH 8.0 and temperature 50°C. Glucose and ammonium carbonate induces enzyme production as carbon and nitrogen sources respectively. Based on the zymographic analysis, the molecular weight of the purified enzyme was about 80 KDa. The alpha galactosidase enzyme produced by Pseudomonas sp MCCMB3 degrades raffinose and stachyose present in soymilk which is used in other industrial applications.